Starch Morphology and Metabolomic Analyses Reveal That the Effect of High Temperature on Cooked Rice Elongation and Expansion Varied in Indica and Japonica Rice Cultivars - Nnaemeka Emmanuel Okpala; Mouloumdema Pouwedeou Potcho; Muhammad Imran; Tianyue An; Gegen Bao; Longxin He; Lin Li; Xiangru Tang (Agronomy, 2021)
Rice (Oryza sativa L.) is mainly grouped into indica and japonica varieties. The aim of this study was to investigate the effect of temperature on cooked rice elongation, cooked rice expansion, and rice fragrance. This study was conducted in three growth temperature chambers with indica cultivar Basmati 385 (B385) and japonica cultivar Yunjingyou (YJY). Grains of B385 grown in low-temperature regimes had the highest cooked rice elongation and expansion, whereas the grains of YJY grown in high-temperature regimes had the highest cooked rice elongation and expansion. Starch granules of B385 grown in low-temperature regimes were more compact and bigger, compared to grains grown in medium- and high-temperature regimes. Conversely, the starch granules of YJY grown in high-temperature regimes were more compact and bigger, compared to those grown in medium- and low-temperature regimes. Metabolomic analyses showed that temperature affected the rice metabolome and revealed that cyclohexanol could be responsible for the differences observed in cooked rice elongation and expansion percentage. However, in both B385 and YJY, grains from low-temperature regimes had the highest 2-AP content and the lowest expression levels of the badh2 gene. The findings of this study will be useful to rice breeders and producers.